Islám a marxismus - vliv na politický vývoj Egypta, Libye a Iráku - Svoboda, Vojtěch (Jihočeská univerzita, 2009)
Socialismus v Egyptě, Libyi a Iráku
Islam and Marxism - The Impact on Political Developments of Egypt, Libya and Iraq
Keywords: arabský socialismus; islám; arabský nacionalismus; al-Bacth; Muslimské bratrstvo; politický vývoj; Egypt; Libye; Irák; Arab Socialism; Islam; Arab Nationalism; al-Bacth; Muslim brotherhood; political development; Egypt; Libya; Iraq